Model of Social and Psychological Adaptation of Women Married to Foreigners - O.I. Mironova; L.A. Ruonala (Психология и право, 2024)
The work is devoted to the study of social and psychological adaptation of women who are married to foreigners. As a result of a theoretical study of the problem, a model of social and psychological adaptation of the social group under the study was firstly formulated and proposed. The model consists of four stages (“honeymoon stage”, stage of accumulation of contradictions, stage of depression, stage of integration), four levels (social level, collective level, personal level, level of close relationships), four types (assimilation, separation, marginalization, integration), four corresponding psychological difficulties (prevailing of the compelled contacts in the structure of communication; women’s expectations regarding interaction with society do not coincide with the expectations of society; ideas about oneself as a migrant before moving do not coincide with real ideas about oneself in the new country; the predominance of external motivation when moving to another country (following the husband), as a consequence — loss of work and familiar surroundings) and clinical manifestations (irritability; frustration, deprivation; depression, somatization; intrapersonal conflict). All of them are interconnected and form a single space of consistent changes in accordance with the tasks of adaptation. A distinctive feature of this model is the emphasis on the dynamic changes in the social and mental sphere of the lives of women-migrants in the process of integration into the host society.